Ответ:
[tex]x=1\frac{3}{10}[/tex].
Объяснение:
[tex]3\frac{8}{15}-(x+1\frac{2}{5})=\frac{5}{6}\\\\3\frac{2\cdot8}{2\cdot15}-(x+1\frac{6\cdot2}{6\cdot5})=\frac{5\cdot5}{5\cdot6}\\\\3\frac{16}{30}-(x+1\frac{12}{30})=\frac{25}{30}\\\\3\frac{16}{30}-x-1\frac{12}{30}=\frac{25}{30}\\\\3\frac{16}{30}-1\frac{12}{30}-\frac{25}{30}=x\\\\2\frac{4}{30}-\frac{25}{30}=x\\\\1\frac{34}{30}-\frac{25}{30}=x\\\\1\frac{9}{30}=x\\\\x=1\frac{9}{30}\\\\x=1\frac{3}{10}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
[tex]x=1\frac{3}{10}[/tex].
Объяснение:
[tex]3\frac{8}{15}-(x+1\frac{2}{5})=\frac{5}{6}\\\\3\frac{2\cdot8}{2\cdot15}-(x+1\frac{6\cdot2}{6\cdot5})=\frac{5\cdot5}{5\cdot6}\\\\3\frac{16}{30}-(x+1\frac{12}{30})=\frac{25}{30}\\\\3\frac{16}{30}-x-1\frac{12}{30}=\frac{25}{30}\\\\3\frac{16}{30}-1\frac{12}{30}-\frac{25}{30}=x\\\\2\frac{4}{30}-\frac{25}{30}=x\\\\1\frac{34}{30}-\frac{25}{30}=x\\\\1\frac{9}{30}=x\\\\x=1\frac{9}{30}\\\\x=1\frac{3}{10}[/tex]